Gold-Catalyzed Intermolecular Carboalkoxylation of Alkenes - Dong, Wenmin; Zhang, Moran; Xiao, Fenfen; Wang, Yunxia; Liu, Wu; Hu, Xiangdong; Yuan, Qiang; Zhang, Shaofei (Synlett, 2012)
A gold-catalyzed intermolecular carboalkoxylation of alkenes has been developed. Readily available and inexpensive dimethyl acetals have been employed as a facile reagent to achieve the carboalkoxylation of alkenes.
Keywords: gold catalysis; carboalkoxylation; alkenes; acetal; 1,3-dimethoxyl compounds